(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article reflects the problems of forecasting tax revenue on types of property taxes from individuals, which are the source of the revenue base of local budgets, and a methodological approach to further improvement of this process.